PENGARUH PENGENDALIAN INTERNAL, INTEGRITAS KARYAWAN DAN KOMITMEN ORGANISASI TERHADAP PENCEGAHAN KECURANGAN - Alfira Tifa Muliza; Christina Dwi Astuti (STMIK Widuri Jakarta, 2023)
This research aims to determine the influence of Internal Control, Employee Integrity, and Organizational Commitment on Fraud Prevention within PT Bank Negara Indonesia Tbk. Jakarta City area. The data for this research were 114 employees from PT Bank Negara Indonesia Tbk. Jakarta City area. This research method is a quantitative research method with primary data obtained from questionnaire data which is measured using an interval scale. The data analysis technique in this research uses multiple linear regression analysis. The results of this research show that Internal Control has no effect on fraud prevention, employee integrity has a positive effect on fraud prevention, Organizational Commitment has a positive effect on fraud prevention.